Fabricação e estudo de um reservatório térmico e de um coletor de grade absorvedora com tubos PVC na configuração em paralelo - Oliveira, Álvaro Luís de (2016)
Solar water heating is one of the main applications of this energy source, because it has already proved that the use of solar heaters can bring significant cost savings to the energy matrix by use of electric showers, large consumers of energy. Within that context was studied a solar water heating system for bath, consisting of a solar collector with pipes and PVC thermal reservoir absorbers made from a polyethylene drum 200 liters. Absorbing tubes were joined by T-connections and knees of PVC, and setting the grid formed absorber was in parallel, to provide greater heating capacity, increasing the temperature of the circulating water. The thermal reservoir composed of polyethylene drum was coated on galvanized steel sheets and between the two surfaces have been applied polyurethane foam, a material of excellent thermal resistance. The proposed heating system had as main features the low cost and simple processes of manufacture and Assembly. Will be presented the processes of manufacture and Assembly of the collector and the heat reservoir, and results of tests that will demonstrate the feasibility of the proposed heating system to promote the heating of water for a shower for a family of four. It was demonstrated that the proposed solar collector had ability to promote pasta water heating thermal tank alternate an average temperature of 49° C, in a single day, well higher than the bathroom, between 32-38° C, and the heating system had autonomy of three baths for a single day of testing. The solar collector heat loss studied was very above on the conventional market solar collectors, but not impeded the use of solar collector proposed for residential uses. The solar heating system alternative studied had cost corresponding to 33,5% of the conventional market, its economic viability.